Factors Affecting Pregnancy Rate Following Fallopian Tube Recanalization in Women with Proximal Fallopian Tube Obstruction - Al-Omari, Mamoon H. (J Clin Med, 2018)
Fallopian tube obstruction is a major cause of female infertility. We aimed to evaluate the factors potentially affecting pregnancy rate following fallopian tube recanalization (FTR) in infertile women with proximal fallopian tube obstruction. Data was retrospectively collected for 61 women (25, primary infertility; 36, secondary infertility) who underwent FTR at our institution. Bivariable and multivariable analyses of clinical pregnancy rates in relation to the following factors were performed: primary vs. secondary infertility, duration of infertility, age at the time of FTR, unilateral vs. bilateral obstruction, and previous pelvic interventions. All women who underwent fluoroscopically guided transcervical FTR of one or both proximally obstructed tubes were successfully recanalized (technical success rate, 100%). Within a year after FTR, 41% of women had conceived. None of the studied variables was significantly associated with pregnancy rate on bivariable analysis. Nevertheless, on multivariable analysis, the type and duration of infertility were significantly associated with pregnancy among women aged <35 years at the time of FTR. Our findings regarding pregnancy rates following FTR reflect the diversity of the patient population and suggest the presence of multiple contributing factors. Younger women with secondary infertility for <5 years are highly likely to achieve conception following FTR.